Roteiros de audiodescrição didática no ensino da matemática na perspectiva inclusiva: tecendo caminhos para o estudante com deficiência visual - Santos, Luciene do Carmo (2025)
This study aims to investigate the application of a pedagogical proposal from the perspective of inclusive education, through the use of didactic audio description scripts for teaching mathematics in basic education. The research was conducted using a qualitative approach, centered on a case study in a public school located in Guarulhos, São Paulo. The participants were two visually impaired students (one in the final years of elementary school and one in high school) and four teachers (two in mathematics, one a specialist in Specialized Educational Services, and one a specialist in Collaborative Teaching). The data were compiled through a literature review, participant observation, semi-structured interviews, and teaching activities, and analyzed systematically and reflectively, as proposed by Minayo (2010). The study seeks to expand research in the area of audio description in the educational context, highlighting it as a pedagogical tool to promote accessibility and remove communication barriers. The research results showed that despite teachers' efforts to promote inclusion in the classroom, there is a significant gap in teacher training related to the use of assistive technologies and the development of formal audio description. It was noted that classroom adaptations are based on oral and ad hoc approaches. A pedagogical guide for mathematics teachers was developed as an educational product. The conclusion is that didactic audio description is a resource that seeks to reconfigure pedagogical practice and strengthen inclusion.